2018
DOI: 10.3390/su10041266
|View full text |Cite
|
Sign up to set email alerts
|

Estimations of Nitrogen Concentration in Sugarcane Using Hyperspectral Imagery

Abstract: Abstract:This study aims to estimate the spatial variation of sugarcane Canopy Nitrogen Concentration (CNC) using spectral data, which were measured from a spaceborne hyperspectral image. Stepwise Multiple Linear Regression (SMLR) and Support Vector Regression (SVR) were applied to calibrate and validate the CNC estimation models. The raw spectral reflectance was transformed into a First-Derivative Spectrum (FDS) and absorption features to remove the spectral noise and finally used as input variables. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…Another research [34], aiming to estimate maize, stated that the RF learner returned the highest accuracies among the evaluated algorithms. For N content, although not conducted in maize crops, multiple types of research [25,33,[53][54][55][56] also concluded that the RF learner, as well as other types of regressors based on decision trees, were appropriate to model LNC. In the presented approach, the errors encountered with this model are relatively lower or similar when in comparison to the aforementioned studies.…”
Section: Discussionmentioning
confidence: 99%
“…Another research [34], aiming to estimate maize, stated that the RF learner returned the highest accuracies among the evaluated algorithms. For N content, although not conducted in maize crops, multiple types of research [25,33,[53][54][55][56] also concluded that the RF learner, as well as other types of regressors based on decision trees, were appropriate to model LNC. In the presented approach, the errors encountered with this model are relatively lower or similar when in comparison to the aforementioned studies.…”
Section: Discussionmentioning
confidence: 99%
“…Similar studies have also been conducted in recent years for sugarcane [19]. Some researchers used satellite imagery [20,21]21 and UAV hyperspectral imagery[22,23] to predict sugarcane biomass and achieved varying degrees of success. However, no reports have been published on nitrogen and irrigation level prediction based on UAV imagery for sugarcane.…”
Section: Introductionmentioning
confidence: 80%
“…They found the prediction accuracy of different approaches in order as PLSR-combined models > PCA-combined models > indices-based models. A non-linear SVR based radial basis function (RBF) kernel predicted critical N concentration in the sugarcane canopy correlated with actual N by R 2 of 0.78 and RMSE of 0.035% [67]. Nutrients with low plant or leaf concentration and subtle physical absorption features still pose a challenge and less attention has been paid for its error-free estimation using remote sensing techniques.…”
Section: Introductionmentioning
confidence: 99%